2021
DOI: 10.1007/s00296-021-04932-1
|View full text |Cite|
|
Sign up to set email alerts
|

Short-term outcomes in children recovered from multisystem inflammatory syndrome associated with SARS-CoV-2 infection

Abstract: Multi-system inflammatory syndrome in children (MIS-C) associated with COVID-19 is a recently recognised potentially life-threatening entity. There is limited data on post-MIS-C sequelae. 21 children fulfilling the WHO criteria for MIS-C were included in our study. Data were collected at baseline and at 12-16 weeks post-discharge to look for any persistent sequelae mainly relating to the lungs or heart including coronary arteries. Fever was the most common presentation, found in 18 (85.7%) patients. All had a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…Twelve studies were conducted in Europe 29-33,36,38-40,44,47,49 and 18 published in 2021 29-33,35-37,39-48 . Thirteen studies used data that were specifically collected for the purpose of the study 29,31-33,35-40,42,45,47,48 , 5 studies used routinely collected data 30,34,41,44,49 and the type of data was unclear in 2 studies 43,46 . Only 2 studies were registered 30,32 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve studies were conducted in Europe 29-33,36,38-40,44,47,49 and 18 published in 2021 29-33,35-37,39-48 . Thirteen studies used data that were specifically collected for the purpose of the study 29,31-33,35-40,42,45,47,48 , 5 studies used routinely collected data 30,34,41,44,49 and the type of data was unclear in 2 studies 43,46 . Only 2 studies were registered 30,32 .…”
Section: Resultsmentioning
confidence: 99%
“…The other 3 controlled studies 30,33,34 had serious risk of bias because negative infection status was determined on the basis of having no documented COVID-19 diagnosis 30 or symptoms 33,34 regardless of laboratory virus detection. Risk of bias due to missing data was serious in 14 studies, because loss-to-follow-up was either>20% 29,31-34,37,39,40,42,43,48,49 or the information provided was unclear 35,38 . One study 41 reported following all participants but used multiple data sources without providing further details and was deemed to be of moderate risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with anti-IL-6R and intravenous immunoglobulin (IVIG) rapidly normalized proinflammatory markers and resulted in good outcomes in a small cohort of patients, but these are not standard therapy (58). In another small cohort of 21 children, who met WHO criteria for MIS-C, all received corticosteroids, while 33% received IVIG (59).…”
Section: Figure 2 Signs Of Multisystem Inflammatory Syndrome In Children (Mis-c) Following Sars-cov-2 Infectionmentioning
confidence: 99%